Dipole force trapping of caesium atoms - Webster, SA; Hechenblaikner, G; Hopkins, SA; Arlt, J; Foot, C (IOP, 2000)
A novel dipole force trap was developed for trapping caesium atoms in the lower hyperfine level of the ground state and in preliminary experiments a cloud of ≈1000 atoms was trapped. The viability of the trap is discussed, including suggestions for amendments to the trap design and problems that might occur which are intrinsic to the caesium atom.